The vertical distribution of Thaumarchaeota in the water column of Lake Malawi inferred from core and intact polar tetraether lipids. (June 2019) - Meegan Kumar, Dervla; Woltering, Martijn; Hopmans, Ellen C.; Sinninghe Damsté, Jaap S.; Schouten, Stefan; Werne, Josef P.
Highlights: Suspended particular matter from Lake Malawi was analyzed for isoprenoid GDGTs. HPH-crenarchaeol concentrations were greatest just below the chlorophyll maximum. Maximum CL concentrations likely reflect degradation of recently produced IPL GDGTs. A second, deeper-dwelling Thaumarchaeotal population exists near the chemocline. Abstract: Several long paleoclimate records generated from Lake Malawi sediments rely on an assumption that the TEX86 paleothermometer reflects annual mean lake surface temperatures. Thaumarchaeota, the producers of the isoprenoid glycerol dialkyl glycerol tetraether (iGDGT) lipids that are the basis of the TEX86 proxy, can occupy a wide range of habitats in the upper water column of lacustrine systems, so it is crucial to specifically constrain the ecology of Thaumarchaeota in Lake Malawi to properly interpret its sedimentary TEX86 record. To investigate the spatial and vertical distribution of Thaumarchaeotal iGDGT production in Lake Malawi, suspended particulate matter (SPM) was collected from the upper water column (>300 m) at three sites spanning the north, central, and south basins of the lake and analyzed for intact polar (IPL) and core (CL) iGDGT lipid abundances. Samples were collected in January during the austral summer when the lake is strongly stratified. Concentrations of the most labile IPL, hexose-phosphohexose (HPH)-crenarchaeol, were greatest just below the deep chlorophyll maximum at ∼50 m water depth in the deeper north and central basins and ∼30 m in the shallow south basin. Maximum CL concentrations occur below the maximum HPH-crenarchaeol concentrations and therefore possibly reflect the accumulation of recently produced IPL GDGT degradation products. If the export of CLs to the sediments is dominated by this CL pool, sedimentary TEX86 would reflect Thaumarchaeota living within the thermocline during the stratified season and therefore may have a cool bias rather than reflecting true surface water temperatures. An increase in abundances of GDGT-2, crenarchaeol isomer, and monohexose (MH)-crenarchaeol at ∼150–200 m suggests that a secondary Thaumarchaeotal population, likely Group I.1b Thaumarchaeota, inhabits the subsurface water column near the anoxic-suboxic boundary. Total production of iGDGTs by this group appears to be much lower than the surface-dwelling clade, but its imprint on sedimentary TEX86 is unknown. An analysis of iGDGT production in the water column throughout the annual cycle is needed to resolve the timing and magnitude of export of CLs to the sediments from these two Thaumarchaeotal populations.